Association of apnea-hypopnea index and lateral cephalometry pre- and post-surgery in obstructive sleep apnea patients - A., Aswini; Mishra, Swati; Modi, Devanshi; Udupi, Sanjay (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Snoring and obstructive sleep apnea are new emerging medical entity and require early diagnosis and treatment because of their increasing implication on physical, mental, social and emotional health. Aim of this study is to assess severity of OSHAS and co-relate efficacy of various post-surgical parameter on objective and subjective improvement in patients. Methods: 43 patients having the symptoms were included in the study and followed over a period of three months and during their post operative visit their lateral cephalometric findings, ESS were recorded and compared to pre operative values to see if any association exists between them. Results: it was seen that various surgical interventions did bring about subjective and objective improvement in patients and these were statistically significant. Conclusions: OSHAS is a spectrum of disorders and has great impact on persons physical, mental and emotional well-being. Early diagnose and treatment eliminated the future risks. Surgical intervention helps improve symptoms of OSHAS and should be undertaken without delay wherever indicated.